Revisiting Hebb: The Mechanisms of Repetition Learning. - Musfeld, Philipp; Oberauer, Klaus (Perspectives on Psychological Science, 2026)
In 1961, Donald Hebb established a classic paradigm for studying repetition learning: He asked participants to remember several memory sets for an immediate serial recall task and repeated one set multiple times throughout the experiment. Participants' ability to recall the repeated set improved gradually with repetitions, thereby demonstrating repetition learning. Explaining this effect has concerned researchers for decades because it provides key insights into how we form durable memory representations through repeated exposure. In this article, we revisit the dominant views on the mechanisms underlying repetition learning, thereby challenging the central assumption that repetition learning is gradual and implicit. We show how these views have emerged from flawed analytical approaches, summarize recent evidence strongly contradicting these claims, and reanalyze previously published data to illustrate how correcting implausible analytical assumptions leads to different theoretical conclusions. We propose an updated theoretical framework of the cognitive mechanisms underlying repetition learning that integrates elements from previous models of the Hebb repetition effect with established models of episodic memory, thereby joining two branches of the memory literature.